Influencing factors and nursing interventions on intraoperative hypothermia in hepatectomy for primary liver cancer (原发性肝癌肝切除术术中低体温相关因素和护理干预研究进展) - HU Ruidan (胡瑞丹); LU Wei (路威); YANG Caihui (杨彩慧); ZHU Xiaoying (朱晓颖) (Association of Integrative Nursing, 2023)
intraoperative hypothermia is a common complication in hepatectomy for liver cancer. This paper analyzed influencing factors of intraoperative hypothermia in hepatectomy for primary liver cancer, summarized nursing countermeasures, and provided reference for prevention of intraoperative hypothermia and its consequence in hepatectomy for primary liver cancer. (术中低体温是肝癌行肝切除术常见并发症。本研究分析导致肝癌行肝切除术术中低体温的相关因素, 总结护理干预措施, 以期为预防术中低体温以及降低术中低体温对肝癌患者造成的损伤提供参考。)